WHISTLEBLOWING SEBAGAI INSTRUMEN PENCEGAHAN FRAUD: PERSPEKTIF AUDITOR INTERNAL - Abdul Gaffar; Darnawati Darnawati; Muhammad Ichsan Gaffar (Universitas Ichsan Sidenreng Rappang, 2026)
The increasing incidence of fraud across public and private organizations indicates that conventional internal control mechanisms are often insufficient to detect and prevent fraudulent activities at an early stage. In this context, a whistleblowing system has emerged as a strategic governance mechanism that enhances organizational transparency, accountability, and fraud prevention. This study aims to explore how internal auditors perceive whistleblowing as an instrument for fraud prevention, identify the factors influencing its effectiveness, and examine the role of internal auditors in fostering an anti-fraud culture. A qualitative research design with a phenomenological approach was employed. Data were collected through in-depth interviews with seven internal auditors, complemented by observations and document analysis. The data were analyzed using thematic analysis involving data condensation, data display, and conclusion drawing. The findings reveal that whistleblowing functions as an effective early warning system for detecting potential fraud. Its effectiveness is strongly influenced by internal auditor independence, whistleblower protection, organizational ethical culture, and management commitment to investigating reported violations. The study contributes to the literature by providing an in-depth understanding of whistleblowing from the perspective of internal auditors through a phenomenological lens, extending previous research that has predominantly adopted quantitative approaches. Practically, the findings emphasize the importance of integrating whistleblowing systems with internal control and fraud risk management to strengthen organizational governance and integrity. Future studies are recommended to involve a broader range of organizations and adopt mixed-methods approaches to enhance the transferability and generalizability of the findings.